Study Literature of Extraction Lipid Method from Microalgae Nannochloropsis sp - Adelya Kristia Putri; Tanti Irma Nuraini; Yustia Wulandari Mirzayanti (IPTEK The Journal of Engineering, 2020)
Biodiesel is a promising alternative fuel obtained from plant oils and animal fats through the esterification process with alcohol. Lipid microalgae Nannochloropsis sp. can be used as raw material for the production of biodiesel or biofuel with oil content in the microalgae Nannochloropsis sp. as much as 21.3 - 32.7% so, it has the potential to be used as a raw material in making biodiesel. Biodiesel produced from microalgae biomass is the most suitable alternative fuel for the future and environmentally friendly fuel. In microalgae lipid extraction, Nannnochloropsis sp. using several process aids such as autoclave, microwave, and soxhlet. Different types of solvents are used to determine the% yield of lipids present in microalgae. Extraction was carried out to compare the extraction method using autoclave, microwave, and soxhlet to obtain the best method that produced the most substantial % lipid. An autoclave obtained the most abundant lipid yield with n-hexane solvent with a ratio of 3: 1 solvent and algal oil. Thus, this review describes the lipid extraction of the microalgae Nannochloropsis sp. with various extraction aids and different solvent types related to lipid production over the past few years.